Changes neuron-specific enolase and protein S100 in the acute period of tick-borne infections in children - G. Yu. Galiyeva; T. V. Poponnikova; T. Yu. Bedareva (Бюллетень сибирской медицины)
We evaluated clinical and laboratory findings in 86 patients of 4—16 years old. Data showed that in all forms of tick-borne infections S100 concentration increased. In meningeal forms of tick-borne infections the S100 level was highest in cases of prolonged progression. The results let conclude that increasing of S100 concentration in all clinical forms of tick-borne infections reflexes the severity of CNS disturbances and their correlation with clinical manifestations.